PERANCANGAN SISTEM INFORMASI DESA BERBASIS WEB PADA KANTOR DESA UJUNG SARIBU - Yohana Natalia Siboro; Resianta Perangin-angin; Eviyanti Novita Purba (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2023)
The Ujung Saribu Village Office is a government agency located in the Pamatang Silimahuta sub-district, Simalungun Regency, North Sumatra Province. In this day and age, the internet has become a necessity that we must fulfill. Through this media, we can get and deliver various data needed anytime and anywhere. Based on observations and interviews, the population data collection system that runs at the Ujung Saribu Village office is still conventional, namely village officials visit people's homes in Ujung Saribu Village to collect data so it takes a long time. The purpose of this research is to assist village officials in the population data collection process and assist the village community in obtaining the required data and information. To produce a village population data collection system that can provide storage and reports quickly and accurately. This website was built using the PHP programming language and MySQL database and tested using black box testing. With the design of the village website, it is hoped that it can assist village officials in entering population data, so that the risk of errors in entering data can be reduced.